2016
DOI: 10.1016/j.jiec.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Activated bentonite as a low-cost adsorbent for the removal of Cu(II) and Pb(II) from aqueous solutions: Batch and column studies

Abstract: © 2015. This manuscript version is made available under the Elsevier user license In this study, the effects of acid activation with high bentonite contents under mild synthetic conditions on textural and structural properties were explored. The alteration features after activation were fully characterized with the help of X-ray powder diffraction (XRD), X-ray fluorescence (XRF), Fourier transform infrared spectroscopy (FT-IR), Scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET) surface area, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(81 citation statements)
references
References 60 publications
(64 reference statements)
4
63
0
10
Order By: Relevance
“…It was observed after analyzing Fig.6.a that the adsorption efficiency increases from 50.45% to 98.25% as pH increases from 2.5 to 11.2. This result suggested that the activated material carried the surface net positive charge below this pH value and it possessed a net negative charge beyond this pH value [54]. For a better illustration of these results, it is required to determine experimentally the point of zero charge (pH PZC ).…”
Section: Batch Adsorption Testsmentioning
confidence: 99%
“…It was observed after analyzing Fig.6.a that the adsorption efficiency increases from 50.45% to 98.25% as pH increases from 2.5 to 11.2. This result suggested that the activated material carried the surface net positive charge below this pH value and it possessed a net negative charge beyond this pH value [54]. For a better illustration of these results, it is required to determine experimentally the point of zero charge (pH PZC ).…”
Section: Batch Adsorption Testsmentioning
confidence: 99%
“…Bentonite is the best adsorbent with high cation exchange capacity, high specific surface area, excellent physical and chemical stability and surface properties (Pawar et al, 2016). It also has good sorption characteristics with respect to heavy metals.…”
Section: +mentioning
confidence: 99%
“…Clay minerals, such as montmorillonite, bentonite, attapulgite, vermiculite, illite, sericite and kaolinite have been used as adsorbents for metals (Pawar et al, 2016), toxins and waste material (Tahir and Naseem, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, petroleum product specifications have become stricter to ensure higher standards of environmental protection [8,[176][177][178][179][180][181][182][183][184][185][186][187]. Large quantities of nickel and sulfur in crude oil make the refining process heavier; unfortunately, the current conventional processes to remove these materials require a significant investment and long reaction times [188][189][190][191].…”
Section: Environmental Applicationsmentioning
confidence: 99%